2018
DOI: 10.1111/1556-4029.13954
|View full text |Cite
|
Sign up to set email alerts
|

Diel Activity and Effect of Carcass Decomposition on the Attractiveness to the Forensically Important SpeciesOxelytrum Discicolle(Coleoptera: Silphidae)

Abstract: Oxelytrum discicolle is a carrion beetle commonly found in the Neotropical region, mainly associated with cadavers and carcasses. Information on behavior related to the likelihood of cadaver colonization is scarce. We performed two field experiments in peri‐urban forest in Brazil in order to strengthen our knowledge on O. discicolle behavior. In the first experiment, we assessed the preference for piglet carcasses at different stages of decomposition offered simultaneously in two seasons, dry and rainy, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
2
2
0
Order By: Relevance
“…The adult presents omnivorous (preferably scavengers), habits and can prey on the larvae of flies and decaying animal substrate, while the immature forms are typically scavengers (Oliva and Di-Iorio, 2008). Recently, experimental ecological studies have shown that O. discicolle presents a high attraction to carcasses in advanced stages of decomposition, and they are more abundant during rainy periods in the Cerrado vegetation (Lira et al, 2019), which supported the use of this species to estimate PMI in the present case, suggesting colonization closer to the date of the victim`s death.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…The adult presents omnivorous (preferably scavengers), habits and can prey on the larvae of flies and decaying animal substrate, while the immature forms are typically scavengers (Oliva and Di-Iorio, 2008). Recently, experimental ecological studies have shown that O. discicolle presents a high attraction to carcasses in advanced stages of decomposition, and they are more abundant during rainy periods in the Cerrado vegetation (Lira et al, 2019), which supported the use of this species to estimate PMI in the present case, suggesting colonization closer to the date of the victim`s death.…”
Section: Introductionsupporting
confidence: 75%
“…This study puts carrion beetles (Silphidae) on par with skin beetles (Dermestidae) and bone beetles (Cleridae), which are regularly mentioned in the forensic literature, mainly in the Neotropical region, since it is the first time that a species of Silphidae has been used to estimate the PMI in the region. Previous research has suggested that when ephemeral resources at different stages of decomposition are available, O. discicolle has a preference for the most decomposed substrate as a source of food, shelter, and oviposition (Lira et al, 2019), similar to the corpse in the present case. The larvae of O. discicolle are typically necrophagous and often found in the lower part of the carcasses, above the hardened soil layer that forms below decomposing corpses in the open air, once the active decomposition begins (Adriana Oliva, personal communication).…”
Section: Case Reportsupporting
confidence: 56%
“…Because of these confusing actions of vertebrates on carcasses, we used iron cages to prevent vertebrates from manipulating forensic entomology experiments with pig carcasses in the Cerrado biome (Faria et al 2018;Lira et al 2019). However, some unanswered questions remain as follows: (i) Which vertebrate species visit and possibly remove or consume carcasses in the Cerrado?…”
Section: Introductionmentioning
confidence: 99%
“…2018; Lira et al . 2019). However, some unanswered questions remain as follows: (i) Which vertebrate species visit and possibly remove or consume carcasses in the Cerrado?…”
Section: Introductionmentioning
confidence: 99%